The Impact of a Training Intervention on Detection of Patient-Ventilator Asynchronies in Nursing Students: Patient-Ventilator Asynchronies in Nursing Students - Gravante, Francesco; Crisci, Franco; Palmieri, Luigi; Cecere, Luciano; Fusi, Cristian; Bulleri, Enrico; Bambi, Stefano (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Patient-ventilator asynchronies (PVA) are associated to negative outcomes for patients: increased respiratory work, mechanical ventilation time and ICU length of stay, and mortality. Some studies described the positive impact of a training intervention on the knowledge and attitudes of nurses in detecting PVA. The aim of this study was to evaluate the efficacy of a training intervention focused on detection of PVA.Methods: A before-after design on a single group of nursing students was used. The training intervention about detection of the correct respiratory waveform through graphic monitoring was conducted in a single edition course of 2 hours, for 25 participants. Measurements of correct detection of PVA through specific competency assessment tool were performed before (T0), immediately after (T1) and at 1 month (T2) from the training intervention between January and February 2020.Results: 19 Nurse students completed the training. A total of 50 questionnaires were distributed (T0; n=19; T1; n=19; T2; n=12). PVA were correctly detected in 67.5% (77) of cases. Statistically significant difference There were differences in trainees performance between T0 and T1 [77,2% (CI95%: 68,7% - 85,8%; p=0.001)] and between T0 and T2 [75% (CI95%: 65,3% - 84,7%; p=0.001]. No significant difference was recorded between T1 and T2 (p=0.83)Conclusions: Nursing students increased their performance on analysis of the graphic monitoring of the respiratory waveforms and detection of asynchronies after a basic training intervention. These skills were retained after 1 month. Nurse student trained about PVA increased their competence potentially employed in critical care settings.